(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Forced marriage is a widespread human rights violation that disproportionately affects women and girls, limiting their autonomy and access to education, economic independence, and personal freedom. This practice is driven by cultural norms, economic hardship, and gender discrimination, making it a persistent challenge in both developing and developed nations. Despite international legal frameworks aimed at eradicating forced marriage, weak enforcement and socio-cultural resistance continue to perpetuate this issue. This paper examines the causes, consequences, and policy recommendations to combat forced marriage and promote gender equality globally.